(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Horticulture is an important part of the agro-industrial complex of Kyrgyzstan and has an important national economic significance. Numerous insect pests and diseases cause the greatest damage to fruit crops. One of the key factors of increasing fruit crops yield is their protection from insect pests and diseases. In recent years, an outbreak of mass reproduction of cherry slimy sawfly (Caliroa cerasi L.), cherry fly (Rhagoletis cerasi L.), winter moth (Agrotis segetum Shiff.), apple moth (Carpocapsa pomonella L.), apple moth (Hyponomeuta malinella L.), gypsy silkworm L. ), gypsy silkworm (Lymantria dispar L.), apple aphid (Aphis pomi Deg.), California shieldworm (Quadraspidiotus perniciosus Comstock), mulberry silkworm (Bombyx mori), leaf curl (Taphrinadeformans (Berk. ) Tul.), bacterial blight (Erwinia amylovora (Burrill) Winslow et al.), parsch (Venturia inaequalis (Cooke) G. Winter), Verticillosis (Verticillium dahliae Kleb.) and powdery mildew (Podosphera leucotricha Salm.) on fruit crops. The article also presents the results of biological efficiency of biological preparation Actarophyte 1,8, which can be successfully used in the control of complex pests of fruit crops.